Development of a Physics Learning Module Based on the Scientific Creativity Project Model Integrated with Artificial Intteligence to Support the Sustainable Development in Education - Maimon Sumo; Nirwana Haidar Hari; El Indahnia Kamariyah; Evangeline D. Pagal (Jurnal Pendidikan Sains Indonesia, 2025)
To support the goals of sustainable development in education (SDGs), it is inseparable from the 21st-century learning framework. 21st-century learning has provided a framework known as 4C, one of which is critical thinking skills (CTS) and creativity. The critical thinking and creativity skills of high school students are still relatively low so they need to be improved. The purpose of this study is to create a suitable learning module (valid, practical, and effective) to support sustainable education. The method used in this study is the development method of Klein and Richey with a one-group pretest-posttest design type, the sample in this study was 180 high school students from various districts in Madura. The research instruments were validation sheets, implementation sheets, and pretest-posttest sheets. The results of this study indicate that the physics learning module integrated with artificial intteligence is proven valid with a validity level reaching 95% in the very valid category. Practically where the implementation of the learning module with this module reaches 95% is well implemented. The effectiveness of the module, with the N-gain analysis results, reached a score of 0.77, categorized as high. This result is reinforced by the results of the effect size test with a score of 0.57, which has a very positive effect on achieving learning objectives. Therefore, this module is suitable for improving CTS and scientific creativity so that it can achieve the SDGs